Enhanced expression of BMP6 inhibits hepatic fibrosis in non-alcoholic fatty liver disease. Issue 6 (10th July 2014) - Arndt, Stephanie; Wacker, Eva; Dorn, Christoph; Koch, Andreas; Saugspier, Michael; Thasler, Wolfgang E; Hartmann, Arndt; Bosserhoff, Anja Katrin; Hellerbrand, Claus
Abstract : Objective: Bone morphogenetic protein 6 (BMP6) has been identified as crucial regulator of iron homeostasis. However, its further role in liver pathology including non-alcoholic fatty liver disease (NAFLD) and its advanced form non-alcoholic steatohepatitis (NASH) is elusive. The aim of this study was to investigate the expression and function of BMP6 in chronic liver disease. Design: BMP6 was analysed in hepatic samples from murine models of chronic liver injury and patients with chronic liver diseases. Furthermore, a tissue microarray comprising 110 human liver tissues with different degree of steatosis and inflammation was assessed. BMP6-deficient (BMP6 −/− ) and wild-type mice were compared in two dietary NASH-models, that is, methionine choline-deficient (MCD) and high-fat (HF) diets. Results: BMP6 was solely upregulated in NAFLD but not in other murine liver injury models or diseased human livers. In NAFLD, BMP6 expression correlated with hepatic steatosis but not with inflammation or hepatocellular damage. Also, in vitro cellular lipid accumulation in primary human hepatocytes induced increased BMP6 expression. MCD and HF diets caused more hepatic inflammation and fibrosis in BMP6 −/− compared with wild-type mice. However, only in the MCD and not in the HF diet model BMP6 −/− mice developed marked hepatic iron overload, suggesting that further mechanisms are responsible for protective BMP6 effect. In vitro analysis revealed that recombinant BMP6 inhibited the activation of hepatic stellate cells (HSCs) and reduced proinflammatory and profibrogenic gene expression in already activated HSCs. Conclusions: Steatosis-induced upregulation of BMP6 in NAFLD is hepatoprotective. Induction of BMP6-signalling may be a promising antifibrogenic strategy.